Evaluation of Radiation Dose and Image Quality in Clinical Routine Protocols from Three Different CT Scanners - Thawatchai Prabsattroo; Jiranthanin Phaorod; Piyaphat Tathuwan; Khanitta Tongluan; Puengjai Punikhom; Tongjit Maharantawong; Waraporn Sudchai (Journal of Imaging)
Computed tomography examination plays a vital role in imaging and its use has rapidly increased in radiology diagnosis. This study aimed to assess radiation doses of routine CT protocols of the brain, chest, and abdomen in three different CT scanners, together with a qualitative image quality assessment. Methods: A picture archiving and communication system (PACS) and Radimetrics software version 3.4.2 retrospectively collected patients’ radiation doses. Radiation doses were recorded as the CTDIvol, dose length product, and effective dose. CT images were acquired using the Catphan700 phantom to evaluate image quality. Results: The findings revealed that median values for the CTDIvol and DLP across the brain, chest, and abdomen protocols were lower than the national and international DRLs. Effective doses for brain, chest, and abdomen protocols were also below the median value of R. Smith-Bindman. Neusoft achieved higher spatial frequencies in brain protocols, while Siemens outperformed others in chest protocols. Neusoft consistently exhibited superior high-contrast resolution. Siemens and Neusoft outperformed low-contrast detectability, while Siemens also outperformed the contrast-to-noise ratio. In addition, Siemens had the lowest image noise in brain protocols and high uniformity in chest and abdomen protocols. Neusoft showed the lowest noise in chest and abdomen protocols and high uniformity in the brain protocol. The noise power spectrum revealed that Philips had the highest noise magnitude with different noise textures across protocols and scanners. Conclusions: This study provides a comprehensive evaluation of radiation doses and image quality for three different CT scanners using standard clinical protocols. Almost all CT protocols exhibited radiation doses below the DRLs and demonstrated varying image qualities across each protocol and scanner. Selecting the right CT scanner for each protocol is essential to ensure that the CT images exhibit the best quality among a wide range of CT machines. The MTF, HCR, LCD, CNR, NPS, noise, and uniformity are suitable parameters for evaluating and monitoring image quality.